2001
DOI: 10.1038/ng726
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a new gene encoding a protein of the hair bundle cause non-syndromic deafness at the DFNB16 locus

Abstract: Hearing impairment affects about 1 in 1,000 children at birth. Approximately 70 loci implicated in non-syndromic forms of deafness have been reported in humans and 24 causative genes have been identified (see also http://www.uia.ac.be/dnalab/hhh). We report a mouse transcript, isolated by a candidate deafness gene approach, that is expressed almost exclusively in the inner ear. Genomic analysis shows that the human ortholog STRC (so called owing to the name we have given its protein-stereocilin), which is loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(142 citation statements)
references
References 19 publications
5
136
0
1
Order By: Relevance
“…16 The deletions in these families at 15q15.3 range from 90 to 100 kb and all include the complete loss of STRC and CATSPER2 at the genomic level. Mutation of STRC causes human nonsyndromic hearing loss at the DFNB16 locus, 27 and CatSper2 À/À male mice are infertile, 22 implicating the disruption of both genes in the pathogenesis of DIS in these human families.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The deletions in these families at 15q15.3 range from 90 to 100 kb and all include the complete loss of STRC and CATSPER2 at the genomic level. Mutation of STRC causes human nonsyndromic hearing loss at the DFNB16 locus, 27 and CatSper2 À/À male mice are infertile, 22 implicating the disruption of both genes in the pathogenesis of DIS in these human families.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 This auditory phenotype is comparable to that observed in persons with DFNB16. 27,28 CatSper and infertility in mice. These clinical presentations are consistent with the phenotypes of CatSper-null mice, which have been described in detail previously.…”
Section: Resultsmentioning
confidence: 99%
“…13 Detailed in silico analysis revealed that although each pair of coding regions shows 498.0% identity, three of the distal genes are likely to be pseudogenes (Figure 2a). The distal copy of KIAA0377 contains only the first 24 of 31 exons, that of SRTC has a stop codon in exon, 22 and that of CATSPER2 differs at numerous positions in the transcript, including CATSPER2, a male infertility gene N Avidan et al base substitutions, gaps and a 1 bp deletion, creating a premature translation termination. CKMT1 is the only gene for which neither the distal nor the proximal copy shows any disruption of coding capacity (the distal copy differs in its cDNA by only two synonymous base substitutions: G1233A and C1263T).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of control chromosome and identification of an B106 kb tandem duplication A detailed analysis of control chromosomes led to the identification, distal to the location of the CDAI linkage interval, of an unsuspected B106 kb tandem duplication, involving four genes ( Figure 2a): (a) The anonymous gene KIAA0377, encoding a 1408 aminoacid-long predicted protein of unidentified function; (b) creatine mitochondrial kinase 1 (CKMT1), which is crucial for energy metabolism, particularly in tissues with high-energy requirements; (c) a transcript expressed almost exclusively in the inner ear, encoding stereocilin (SRTC) 22 and (d) CATSPER2, a sperm-specific voltage-gated cation channel. 13 Detailed in silico analysis revealed that although each pair of coding regions shows 498.0% identity, three of the distal genes are likely to be pseudogenes (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation